Menganalisis Struktur Batin Puisi “Selamat Tinggal” Karya Chairil Anwar - Welly Karmelia; Jelwita Waruwu (Jurnal Pendidikan Bahasa dan Anak Usia Dini, 2025)
This research aims to analyze the inner structure in the poem "Goodbye" by Chairil Anwar, a leading poet in Indonesian literature. The poem was chosen because of its ability to arouse emotions and contain deep meaning. With the background of Chairil Anwar who lived during a time of political and social turmoil, analysis of the inner structure of this poem can provide insight into how the poet reflects his feelings towards separation in that context. The research method used is literary analysis with a qualitative approach. By understanding the imagery, symbolism and emotional tone contained in the poem "Goodbye", this research tries to explore the feelings implied behind Chairil Anwar's words. The findings from this analysis reveal the depth of emotion and sadness in the poem, as well as the way the poet expresses his feelings through beautiful and poetic language. The implication of this research is to broaden understanding of Indonesian literary works and the richness they contain. Analysis of the inner structure of the poem "Goodbye" can contribute to appreciating the literary value and beauty of the poet's expression, as well as enriching the interpretation of Indonesian literary works as a whole.